The spatiotemporal changes of crab community in the Yangtze River Estuary after the fishing ban - Yang, Zuchang; Feng, Guangpeng; Yang, Gang; Zhang, Tao; Zhao, Feng; Geng, Zhi; Li, Xia; Tan, Qingyuan (Frontiers in Marine Science, 2024)
The Yangtze River Estuary is the traditional habitat of fishery resources in China and also one of the crab fishing sites, but nowadays the crab resources have been seriously affected by highintensity anthropogenic disturbance. To understand the composition and diversity of crab community following the fishing ban, six surveys were conducted from August 2022 to November 2023 using the single-bag trawl method. This study examined the crab community composition, biodiversity, resource density, spatiotemporal distribution patterns, and main influencing factors.Results indicated that a total of 14 crab species lived in the Yangtze River Estuary. Matuta planipes and Portunus trituberculatus were dominant crabs in summer 2022. P. trituberculatus, Eriochier leptognathus, and Charybdis japonica were dominant crabs in autumn 2022. Then, E. leptognathus and Eriocheir sinensis were dominant crabs in winter 2023. Notably, the largest numbers of dominant crabs appeared in spring 2023, including M. planipes, P. trituberculatus, E. leptognathus, C. japonica, and E. sinensis. Three same dominant crabs (M. planipes, P. trituberculatus, C. japonica) were identified in the summer and autumn of 2023. Thereinto, P. trituberculatus was the most dominant crab. The abundance and biomass trends of estuary crabs were winter < spring < autumn < summer. The community diversity index, evenness index, and richness index were winter < summer < autumn < spring, indicating the seasonal changes in abundance, biomass, and biodiversity. Correlation and redundancy analysis revealed that dissolved oxygen and salinity were the most critical environmental factors, which affect the changes in crab community in the estuary.This study revealed the changing characteristics of crab resources in the Yangtze River Estuary after the fishing ban, and provided the essential data and scientific basis for resource conservation and management decisions.